Influence of metal structural heterogeneity on corrosion of steam boiler pipes; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 4 : Power engineering - Zavorin A. S. Aleksandr Sergeevich; Lyubimova L. L. Lyudmila Leonidovna; Makeev A. A.; Tashlykov A. A. Aleksandr Anatolievich; Artamontsev A. I. Aleksandr Ivanovich; Lebedev B. V. Boris Vladimirovich; Макеев А. А. Анатолий Анатольевич (Power engineering, 2007)
Заглавие с титульного листа